(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate, in vitro, through microhardness and roughness analysis, the action of a desensitizing agent on tooth enamel before and/or after being subjected to tooth whitening. Forty bovine incisors were used to obtain 40 enamel fragments. The samples were divided into 5 experimental groups (n = 8): positive control - without bleaching treatment, negative control - bleaching agent, G1 - bleaching + desensitizing agent, G2 - desensitizing + bleaching agent, G3 - desensitizing + bleaching + desensitizing agent. Three applications were made, 8 minutes each, of the bleaching gel and 1 application of 10 minutes of desensitizing. The treatments followed sequences according to the experimental groups. Before the treatments were carried out, the samples went through 3 readings of surface roughness and microhardness, which were repeated after the treatments. The data were tabulated and submitted to statistical analysis ANOVA, Tukey, Wilcoxon and Dunnett’s test, considering the treatment and time factors. The statistical analysis of the data revealed that, although there was a decrease in roughness, there was no statistically significant difference before and after the application of the desensitizing agent and whitening gel.